2016
DOI: 10.1177/0021998316669855
|View full text |Cite
|
Sign up to set email alerts
|

The increased compression strength of an epoxy resin with the addition of heat-treated natural nano-structured diatom frustules

Abstract: Natural diatom frustules composing nanometer size silica particles were heat-treated at temperatures between 600 and 1200℃ for 2 h and used as filler/reinforcing agent (15 wt%) in an epoxy resin. The opal structure of as-received natural diatom frustules was transformed into cristobalite after the heat-treatment above 900℃. The epoxy resin test samples reinforced with heat-treated and as-received frustules and neat epoxy test samples were compression tested at the quasi-static strain rate of 7 × 10−3 s−1. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a previous study, the compressive modulus and yield strength of an epoxy matrix were shown to increase with the diatom frustule addition and the stress enhancement of filled epoxy was ascribed to relatively high strength of frustules and strong interlocking between the frustules and the polymer matrix [5,14]. It was also shown that the filling the epoxy matrix with the heat-treated frustules at a certain temperature maximized the matrix strengthening of the composite [15]. The present study is a continuation of the previous studies and aims to investigate the effect of diatom frustules' shape and size on the compression stress-strain behavior of a polymer matrix at quasi-static strain rate.…”
Section: Introductionmentioning
confidence: 93%
“…In a previous study, the compressive modulus and yield strength of an epoxy matrix were shown to increase with the diatom frustule addition and the stress enhancement of filled epoxy was ascribed to relatively high strength of frustules and strong interlocking between the frustules and the polymer matrix [5,14]. It was also shown that the filling the epoxy matrix with the heat-treated frustules at a certain temperature maximized the matrix strengthening of the composite [15]. The present study is a continuation of the previous studies and aims to investigate the effect of diatom frustules' shape and size on the compression stress-strain behavior of a polymer matrix at quasi-static strain rate.…”
Section: Introductionmentioning
confidence: 93%
“…The development of composites using diatomite as siliceous fillers is an alternative to the sintering technique for advanced diatomite-based material prospects. Examples of composites using diatomite in various types of polymeric matrices such as epoxy [9], polyacrylate [10], polyetherimide [11], polyurethane [12], polylactide [13], chitosan [14], or different kinds of rubber [15] have shown the improvement of thermal stability and mechanical properties of composites. In these researches, the fillers have been incorporated at a rate not exceeding 15% by weight for the mechanical reinforcement purpose.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the proportion of the petroleum-based polymers in engineering materials, the research, and application of bio-composites can solve this problem, while allowing the use of natural raw materials. [1][2][3][4][5][6] As an essential industrial raw material, epoxy resins are widely used as matrices in many applications such as coatings, adhesives, electronic materials, and printed circuit boards due to their low shrinkage, good chemical resistance, hydrophobicity, electrical insulation, and other outstanding properties. [7][8][9][10][11][12][13][14] However, the brittleness and high dielectric constant limit the application of epoxy resins in the fields of integrated circuits and semiconductors.…”
Section: Introductionmentioning
confidence: 99%